2013
DOI: 10.1002/anie.201207731
|View full text |Cite
|
Sign up to set email alerts
|

[(μ‐C){Re(CO)2(η‐C5H5)}2]: A Surprisingly Simple Bimetallic Carbido Complex

Abstract: The bonding in the majority of binuclear m-carbido complexes may, to a first approximation, be described by one of two extreme canonical forms (A and B; Scheme 1). Symmetrical bimetallic complexes in which similar metal centers are bound to the central carbon atom are generally considered to adhere to a dimetallaallene-like bond localization (class A). [1,2] Most examples of this type of bonding have so far arisen from the reduction of Group 8 porphyrin complexes in the presence of CI 4 ; [1] this synthetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 34 publications
1
21
0
1
Order By: Relevance
“…The rhodium–carbon bond lengths [Rh1–C1 1.788(4), Rh2–C1 = 1.798(4) Å] are in a typical range for Rh=C bond lengths when compared to carbene and vinylidene complexes . Iron carbido complexes show in contrast to 9 shorter metal–carbon bonds, whereas Rh, Re, Ru, and Nb complexes exhibit comparable values , ,. [20a], b The bond lengths and angles of the structurally related rhodium µ‐carbido complex trans , trans ‐[Rh 2 (µ‐C)(SBpin) 2 (PEt 3 ) 4 ] ( 10 ) are very similar .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rhodium–carbon bond lengths [Rh1–C1 1.788(4), Rh2–C1 = 1.798(4) Å] are in a typical range for Rh=C bond lengths when compared to carbene and vinylidene complexes . Iron carbido complexes show in contrast to 9 shorter metal–carbon bonds, whereas Rh, Re, Ru, and Nb complexes exhibit comparable values , ,. [20a], b The bond lengths and angles of the structurally related rhodium µ‐carbido complex trans , trans ‐[Rh 2 (µ‐C)(SBpin) 2 (PEt 3 ) 4 ] ( 10 ) are very similar .…”
Section: Resultsmentioning
confidence: 99%
“…of the highly reactive rhodium boryl complex [Rh(Bpin)(PEt 3 ) 3 ] ( 7 ) with CS 2 leading to the formation of a dinuclear rhodium µ‐carbido complex trans , trans ‐[Rh 2 (µ‐C)(SBpin) 2 (PEt 3 ) 4 ] ( 10 ) . Comparable fragmentation reactions breaking both C–S bonds in CS 2 are scarce . However, the stoichiometric conversion of 7 with CS 2 led to the formation of the thiocarbonyl complex [Rh(SBpin)(CS)(PEt 3 ) x ] ( x = 2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the simple μ‐carbido complex [Re 2 (μ‐C)(CO) 4 (η‐C 5 H 5 ) 2 ] has a negligible rotation barrier (ca. <16 kJ mol −1 ), which is attributed to the bonding being better described as a 2σ,4π 3‐center, 12‐electron system which is not significantly disrupted at any rotational angle . To further test the allene analogy, one might ask how the nature of the μ‐carbido center might respond to departure from linearity: Is there a μ‐carbido version of a bent allene?…”
Section: Methodsmentioning
confidence: 99%
“…4 Cyclopentadienyl tricarbonyl rhenium (I), 1, is the next commercially available complex in the group 7 series (with the technetium analogue being radioactive), 5 that we wished to focus our attention upon. The applications of cyclopentadienyl rhenium(I) tricarbonyl, 1, have recently been reported in a wide array of research areas, including examples that have shown the photolysis of CO ligands allowing the coordination of new ligands (CS 2 , PPh 3 ), 6 utilizing the CO ligands of 1 as non-natural labels for probing protein electrostatics, 7 and modification of the cyclopentadienyl moiety to allow the formation of new cyrhetrene complexes with bidentate ligands, capable of forming new palladacycles. 8 Geiger has previously investigated the anodic behaviour of cyclopentadienyl tricarbonyl rhenium(I) 1, and has shown that the half-cell potential for the cyclopentadienyl tricarbonyl rhenium(I) redox couple +1/+2 is +1.16 V vs the ferrocene/ferricenium couple.…”
Section: Introductionmentioning
confidence: 99%
“…8 Geiger has previously investigated the anodic behaviour of cyclopentadienyl tricarbonyl rhenium(I) 1, and has shown that the half-cell potential for the cyclopentadienyl tricarbonyl rhenium(I) redox couple +1/+2 is +1.16 V vs the ferrocene/ferricenium couple. 9 Interestingly, this oxidation is only partly reversible in CH 2 Cl 2 (with [n-Bu 4 N][B(C 6 F 5 ) 4 ] as the supporting electrolyte), 10 due to the formation of the dimer, [Re 2 Cp 2 (CO) 6 ] 2+ , which shows an irreversible cathodic wave around ca 0.55 V vs the ferrocene/ferricenium couple. Furthermore, the use of [ReCp(CO) 3 ] + , 1 + , as a strong one-electron oxidant proved to be an excellent electron-transfer mediator in the case of coupling unactivated olefin substrates.…”
Section: Introductionmentioning
confidence: 99%